Diversity Management and Performance of Academic Staff of Public Higher Institutions in Anambra State, Nigeria - Nwanze, Chinwe Judith (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examines the effect diversity management and performance of academic staff of public higher institutions in Anambra State, Nigeria. The specifically investigate the effect of ethnic diversity on task performance; religion diversity on the adaptive performance and cultural diversity on the contextual performance. Three research questions and three hypothesis were formulate in line with the objective. Relevant conceptual, theoretical and empirical literatures were review. This study is anchored on institutional theory. The study adopted descriptive survey research design. Data were source from primary and secondary sources. The population of the study comprised 4593 academic staff of the public higher institutions in Anambra State. Sample size of eight hundred ninety-six 896 respondents using Borg and Gall (1973) formula. Questionnaire was employed as the main instrument of data collection. Face and content validity of the questionnaire was adopted using experts’ judgment. Test re-test and Cronbach Alpha was used to test the reliability of the instrument. The data generated were analyzed using simple percentage analysis and Simple Regression analyses was use in testing the hypotheses. The study found that ethnic diversity has a significant effect on task performance of academic staff; religion diversity had a significant positive effect on adaptive performance of academic staff of public higher institutions; cultural diversity had a positive significant effect on contextual performance of academic staff of public higher institutions; gender diversity has a significant positive effect on employee effectiveness of academic staff of public higher institutions and age diversity has a significant positive effect on employee competence of academic staff of public higher institutions in Anambra State, Nigeria. The study concluded that diversity management had a positive significant effect on the performance of academic staff of public higher institutions in Anambra State, Nigeria. The recommended that public higher institutions should conduct a training on how to minimize communication barriers by conducting a seminar on ethical diversity will also come in handy to curb the ethical conflict that arises from diversity in ethnicity. In order to avoid a high employee turnover, there is a dire need to ensure that all employees are given an opportunity to practice their religion. In order to avoid conflict management of public higher institutions should adopted cultural values in line with the employee cultural.